Pemerolehan Bahasa Tulis Produktif Anak Kelompok Bermain dan Taman Kanak-kanak - Tadkiroatun Musfiroh (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
Achieving Competence in children's productive written language (PWL) in playgroup and kindergarten indicates the existence of language acquisition, based on the 8 principles (differentiation, symbolization, integration, imitation, variation, inventarization-collection, repetition, generating). This acquisition process is categorized into 8 stages (scribble, linear repetitive, like-letter, random letter, early spellings, phonetic, transitional, conventional). The majority of subjects make handwriting which covers the forms of leaning-corrupted-interpolated-like-letter form, mirrored, and shadowed form. Children's PWL acquisition is related to children engagement in written language activities, social interaction, and exposure.